Corporate governance and earnings management: evidence from PN17 companies in Malaysia / Aida Maria Ismail and Wee Xian Xing - Ismail, Aida Maria; Wee Xian, Xing (Faculty of Accountancy, 2019)
There have been many studies regarding the connection of corporate governance mechanisms on the Earning Management (EM) practices. However, the results from the studies are mixed and require further research. The interest for EM practices becomes more important to the investors for them to avoid any financial losses. This paper examine the relationship of corporate governance mechanisms in terms of board independence, total number of board members, frequency of board meetings, directors’ shareholdings and frequency of audit committee meetings towards the EM practices among financial distressed companies in Malaysia. Logistic regression was used to determine the correlations that exist between the variables. The data used in this paper were 36 companies from Practice Note 17 listed on the Bursa Malaysia Website during the period of 2014- 2018. This period has been chosen due to the establishment of Malaysia Code of Corporate Governance (MCCG) 2015 and 2017. By testing five hypotheses, the results showed that there were all negative relationship between board independence, total number of board members, , the frequency of board meetings being held, the total directors’ shareholdings and frequency of audit committee meetings towards the EM practices and do not significantly affect the likelihood of earnings manipulation. This paper consequently outlined the important mechanisms that will give an impact on the EM practices. In relation to this, the corporate governance mechanisms should be highlighted as a few of the factors can ensure the interests of investors are protected.